Health assessment of Arsenic and Zinc in rice cultivated in Fars province (Case Study: Firoozabad fields) - M Anvarinejad; H Mirzaei (Bihdāsht-i Mavādd-i Ghaz̠āyī, 2013)
Food security along with the protection of environment has become a global issue.Accumulation of Arsenic and Zinc in rice is considered as a major problem for South-East Asia, where rice is a staple food. Given that, rice is considered as the highly consumed food in the diet of Iranian people, this study was conducted to estimate the concentrations of Zinc and Arsenic in rice cultivated in Firoozabad fields. For this purpose, 38 rice samples were collected from 22 nearby villages. Samples were digested by Digesdahl device and the concentrations of Arsenic and Zinc were determined by ICP. The results showed that the concentration (mean ± SD) of Zinc was 20.87 ± 1.9 mg/kg of dry matter (ranged from 25.26 to 32.97); meanwhile mean value of Arsenic concentration was estimated at 22.89 ± 2.2 mg/kg of dry matter (ranged from 17.61 to 26.77).Comparing the concentrations of Arsenic and Zinc in rice samples with the standard limit set by WHO/FAO it was revealed that Arsenic concentrations in 100% of the samples were higher than standard level, whereas Zinc concentrations in 97.36% of the samples were below the limit.